Assessment of Kelantan River water quality using water quality index (WQI). Issue 1 (August 2021) - Radin Nizar, F S; Mohd Ghazi, R; Awang, N R; Muhammad, M
Abstract: Kelantan River is the main river in Kelantan, and it has been used for water sources for irrigation, small-scale fishing industries, transportation, and sand mining. WQI is a comprehensive method for displaying water quality status and achieving good water quality. This study is aims to identify the significant difference in water quality index (WQI) parameters and the correlation between WQI parameters in urban, suburban, and residential area along the Kelantan River from 2015 until 2019. Water quality stations in urban, suburban, and residential areas were selected with facilitation of ArcMap 10.0 software. In this study, Kota Bharu represented urban area, Kuala Krai represented suburban area and Tanah Merah represented residential area. The significant difference between WQI value with different stations were determined using analysis of variance (ANOVA). Meanwhile the correlation between WQI parameters were determined using Pearson correlation. From this research, there is no significant difference in water quality between urban, suburban, and residential areas along Kelantan River. The correlation of water quality parameters varies between locations which indicates different water pollution contributors except correlation between biochemical oxygen demand (BOD) and chemical oxygen demand (COD), pH and ammoniacal nitrogen (AN), and total suspended solid (TSS) and WQI. WQI in urban, suburban, and residential areas were classified in Class II from 2015 until 2019 except WQI in residential area in 2019 which was classified in Class III. This study will provide scientific reference for future use to protect local aquatic environment in Kelantan River and can be used to manage the river basin development in future.